Pola Komunikasi Kader Posyandu Lansia (Studi Kasus Posyandu Lansia Mawar Kelurahan Kebon Kacang) - Zubedi, Rifad; S. Gassing , Syarifuddin (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Communication patterns are a communication process used by an individual or group in conveying amessage. Communication patterns in delivering a message are concerned with how posyandu cadres provideinformation to the elderly through the posyandu cadre factor listening to complaints, providing direction, andmotivating which encourages the elderly to be more open in communicating The theory used in this study is SelfDisclosure Theory. The theory reveals self-disclosure in interpersonal communication related to communication patterns,posyandu cadres, the elderly, and self-disclosure. The research method used is a case study using a qualitativeresearch approach. The type of research used is descriptive research. Data collection techniques used through in-depthinterviews with several informants, as well as observations supported by literature studies. The results of this study are communication patterns carried out by posyandu cadres through self-disclosureto the elderly. With self- disclosure, posyandu cadres can provide the right solution and provide comfort to theelderly in communication.